Analysis of Furniture Product Defects Using Fault Tree Analysis and Root Cause Analysis Methods - Sofia Fitri Anasari; Rr. Rochmoeljati (Journal La Multiapp, 2025)
PT WW is a furniture company that uses teak wood as its main material. Factory 1 often experiences product defects because it handles the initial production stage. This study focuses on the SP-15 chair, the company’s best-selling product, which has a defect rate of 15.2%, far above the company tolerance of 5%. The research aims to reduce these defects using the Fault Tree Analysis (FTA) method and provide improvement recommendations. Observations revealed three defect categories with eleven basic causes. The most dominant defect is rupture, with 2726 units and a probability of 0.0085 or 0.85%. Meanwhile, the lowest defect type is incorrect process, with 835 units and a probability of 0.0034 or 0.34%. Because rupture has the highest probability, improvement efforts are urgently needed. Proposed corrective actions include developing and applying SOPs for wood processing, installing visual guides in the work area, establishing standard work procedures, and providing short operator training. Additional recommendations include routine technical training and competency tests, guidelines for machine pressure settings based on wood type, and operator instruction on adjustment. Regular maintenance schedules should also be established, with visual operation guides placed near machines to ensure operators follow correct steps. These efforts are expected to reduce defects and improve the quality of SP-15 chair production at PT WW.